QUALIFICATIONS OF HIGHER EDUCATION AND PROFESSIONAL QUALIFICATIONS: HARMONIZATION WITH EFFORTS - E. V. Karavaeva (Высшее образование в России)
The paper focuses on the topical problem of harmonization of professional and educational qualifications. Based on the analysis of the international practice (US experience), the author considers the attempts to couple professional standards and federal state educational standards and shows their inadequacy. The paper dwells on the peculiarities of the Russian National qualifications system formation and comes to a conclusion that owing to the absence of the modern sectoral qualifications frameworks in Russia it is impossible to accomplish the harmonization of labour market requirements and university graduates’ competences.